Surgical Correction of Craniofacial Microsomia: Evaluation of Interventions in 565 Patients at Three Major Craniofacial Units - Pluijmers, Britt I; Caron, Cornelia J J M; van de Lande, Lara S; Schaal, Sontje; Mathijssen, Irene M; Wolvius, Eppo B; Bulstrode, Neil; Evans, Robert D; Padwa, Bonnie L; Koudstaal, Maarten J; Dunaway, David J (Plastic and reconstructive surgery (1963), 2019)
Craniofacial microsomia is characterized by an asymmetric hypoplasia of derivatives of the first and second pharyngeal arch, leading to a variety of phenotypic presentations. Studies on surgical correction of patients with craniofacial microsomia have small cohorts, leaving controversial opinions on the optimal treatment modality, the indication for surgery, and the optimal timing of surgery. The purpose of this study was to evaluate the types of, timing of, and total number of surgical corrections performed and the number of surgical procedures in correlation to the severity of the phenotype. A retrospective chart study was conducted including patients diagnosed with craniofacial microsomia from three large craniofacial units. Demographic, radiographic, and clinical information was obtained, including type and number of surgical procedures and age at the time of surgery. A total of 565 patients were included. In total, 443 (78.4 percent) of all patients underwent some form of surgery during their life, varying from skin tag removal to major craniofacial operations. The number of surgical interventions was higher with increasing severity of phenotype, bilateral presentation, and a younger age at the first intervention. Multiple surgical corrections are frequently seen in patients with a more severe or bilateral presentation. Furthermore, those who are treated earlier in life for correction of asymmetry of the mandible will undergo significantly more surgical procedures to correct the asymmetry later on, independent of the Pruzansky-Kaban type mandible. A prospective international multicenter study is designed with a uniform registration and outcome measurement tool to identify the optimal treatment strategy.